Advances in processing and characterization of conversion coatings - Jelena Bajat (Journal of Electrochemical Science and Engineering, 2022)
The present special issue of the Journal of Electrochemical Science and Engineering presents contributions on various kinds of non-toxic conversion coatings on different metal substrates: steel, stainless steel, zinc, copper, aluminum, and the broad range of their properties and applications. Different functions require surface science and surface engineering at a molecular level and are related to the chemical, phase and morphological nature of their surfaces.